2014
DOI: 10.7600/jpfsm.3.445
|View full text |Cite
|
Sign up to set email alerts
|

Role of serotonergic system in thermoregulation in rats

Abstract: The neurotransmitter serotonin (5-hydroxytryptamine, 5-HT) is involved in the regulation of several basic physiological functions such as hormone secretion, sleep-wake cycle, motor control, immune system functioning, nociception, food intake, energy balance and thermoregulation. In addition, 5-HT participates in higher brain functions, such as cognition and emotional states, by modulating synaptic plasticity and neurogenesis. Furthermore, 5-HT has recently captured the spotlight in connection with depression, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The change in body temperature of warm-blooded organisms is also one of its physiological effects. 5-HT receptors that definitely influence the body temperature of a warm-blooded organism are the following: the 5-HT receptor of the 1A type (5-HT 1A ), the 5-HT receptor of the 2 type (5-HT 2 ), the 5-HT receptor of the 3 type (5-HT 3 ), and the 5-HT receptor of the 7 type (5-HT 7 ) [ 18 , 19 , 27 , 30 , 31 ]. The present article focuses solely on these receptors and their role in body temperature maintenance of warm-blooded organisms.…”
mentioning
confidence: 99%
“…The change in body temperature of warm-blooded organisms is also one of its physiological effects. 5-HT receptors that definitely influence the body temperature of a warm-blooded organism are the following: the 5-HT receptor of the 1A type (5-HT 1A ), the 5-HT receptor of the 2 type (5-HT 2 ), the 5-HT receptor of the 3 type (5-HT 3 ), and the 5-HT receptor of the 7 type (5-HT 7 ) [ 18 , 19 , 27 , 30 , 31 ]. The present article focuses solely on these receptors and their role in body temperature maintenance of warm-blooded organisms.…”
mentioning
confidence: 99%
“…Du ( 54 ) reported that the blood IL-6 have decreased in the heat-stress healing group. Additionally, 5-HT plays a key role in the central thermoregulatory system ( 55 ). There were no differences in plasma HSP-70, HSP-90, GLU, IL-6, PRL, and 5-HT between HTDC and HSDC in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In our experiment, the heat-tolerant cows had the same result. The central nervous system regulates the reactions of thermoregulatory effectors, such as cutaneous circulation, brown adipose tissue, and sweat glands, to external temperature challenges; 5-HT is thought to play a key function in this core thermoregulatory system [ 43 ]. In the rat hypothalamus, short-term HS accelerates 5-HT metabolism and increases the expression of 5-HT receptor genes [ 44 ].…”
Section: Discussionmentioning
confidence: 99%